Development and Evaluation of an iiPCR Assay for Salmonella and Shigella Detection on a Field-Deployable PCR System. (7th September 2020) - Du, Tian; Lin, Ji-hong; Zhao, Jun-hua; Wang, Hai-bo; Mo, Qiu-hua
Abstract : Background . Salmonella and Shigella are often associated with fecal-oral transmission and cause large-scale outbreaks in centralized catering units and, therefore, should be frequently and strictly monitored, especially among food handlers. However, no specific and sensitive on-site detection method is available until now. Methods . In this study, an insulated isothermal PCR assay for the detection of Salmonella and Shigella on a field-deployable PCR system was developed. Specificity, sensitivity, reproducibility, and clinical accuracy of the assay were characterized and evaluated. Results . The insulated isothermal PCR assay could be completed within 58 minutes with minimal pretreatment needed. The assay was specific and with good reproducibility. The limit of detection was 10 3 CFU/mL and 10 1 CFU/mL for Salmonella and Shigella, respectively, which was comparable to multiplex real-time PCR. Mock on-site clinical evaluation results showed that the analytical sensitivity and specificity of the insulated isothermal PCR assay were 100% and 96.6%, while the positive predictive value and negative predictive value were 94.1% and 100%, respectively. Conclusion . Based on our results, we believe that the assay developed herein could serve as an alternative method for preliminary screening and provide a valuable platform for the on-site detection of Salmonella and Shigella, especially in resource-limited and developing countries.